PENERAPAN SISTEM BUDIDAYA IKAN BERKELANJUTAN DENGAN KONSEP NATURAL PADA RESTORASI LINGKUNGAN, SOSIAL DAN PEREKONOMIAN KAMPUNG NELAYAN KAMAL MUARA - Wilianto, Juan Nathanie; Sutanto, Agustinus (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
Kampung Nelayan Kamal Muara, once a vibrant coastal community, is now ensnared in environmental and social degradation. Marine pollution, reclamation, and excessive exploitation of natural resources have triggered the death of marine life, habitat destruction, silting, and changes in ocean currents. This has not only taken away livelihoods and economies but also a sense of security, connection to the environment, cultural identity, and has the potential to turn Kamal Muara into a "placeless place." This research aims to combat degradation and rebuild a sense of place in Kamal Muara through sustainable aquaculture architecture. Literature studies have shown that sustainable aquaculture offers an innovative solution to restore coastal ecosystems, improve seawater quality, and empower communities. The research method combines qualitative and quantitative approaches. Data is collected through surveys, interviews, observations, and secondary data analysis. The results show that the aquaculture system in Kamal Muara can increase marine biodiversity, seawater quality, and fishermen's income. This system can also strengthen cultural identity and traditions. This research proves aquaculture to be an effective strategy for restoring coastal ecosystems and empowering communities in Kamal Muara. Sustainable aquaculture architecture focuses not only on ecological and economic functions but also on social and cultural aspects. Architectural designs that are sensitive to the local context and community needs can help rebuild a sense of place in Kamal Muara, counteract the phenomenon of "placelessness," and create meaningful spaces for this coastal community. Keywords:  Environmental degradation; Kamal Muara Fishing Village; Marine pollution ; Placeless place; Sustainable aquaculture Abstrak Kampung Nelayan Kamal Muara, dahulu komunitas pesisir yang dinamis, kini terjerat degradasi lingkungan dan sosial. Pencemaran laut, reklamasi, dan eksploitasi sumber daya alam berlebihan memicu kematian biota laut, kerusakan habitat, pendangkalan, dan perubahan arus laut. Hal ini tak hanya merenggut mata pencaharian dan ekonomi, tapi juga rasa aman, keterikatan dengan lingkungan, identitas budaya, dan berpotensi menjadikan Kamal Muara sebagai "placeless place". Penelitian ini hadir sebagai upaya melawan degradasi dan membangun kembali rasa tempat di Kamal Muara melalui arsitektur akuakultur berkelanjutan. Kajian literatur menunjukkan akuakultur berkelanjutan menawarkan solusi inovatif untuk memulihkan ekosistem pesisir, meningkatkan kualitas air laut, dan memberdayakan masyarakat. Metode penelitian menggabungkan kualitatif dan kuantitatif. Data dikumpulkan melalui survei, wawancara, observasi, dan analisis data sekunder. Hasil menunjukkan bahwa sistem akuakultur di Kamal Muara dapat meningkatkan keanekaragaman hayati laut, kualitas air laut, dan pendapatan nelayan. Sistem ini pun dapat memperkuat identitas budaya dan tradisi.Penelitian ini membuktikan akuakultur sebagai strategi efektif dalam memulihkan ekosistem pesisir dan memberdayakan masyarakat di Kamal Muara. Arsitektur akuakultur berkelanjutan tak hanya berfokus pada fungsi ekologis dan ekonomi, tetapi juga aspek sosial dan budaya. Desain arsitektur yang sensitif terhadap konteks lokal dan kebutuhan masyarakat dapat membantu membangun kembali rasa tempat di Kamal Muara, menangkal fenomena "placeless place", dan menciptakan ruang yang bermakna bagi komunitas pesisir ini.